Kebebasan Berpendapat dan Kaitannya Dengan Hak Asasi Manusia (HAM) - Ersa Kusuma (Sanskara Hukum dan HAM, 2023)
As Article 28E (3) of the 1945 Constitution states that everyone has the right to freedom of association, assembly and speech. The purpose of this writing, among other things, is to find out that there is still a lot of freedom of expression which has experienced a narrowing of the public sphere, both verbally and in writing; to examine that in Indonesia there are still many cases that threaten freedom of expression thereby violating the human rights contained in the 1945 Constitution. The research method used is library research, in legal research the normative jurisprudence method is based on statutory provisions such as regulations on human rights books as well as from research magazines related to the subject matter and information from websites related to research titles. this. Research has found that recently freedom of speech sometimes makes sense only for constructive criticism of people, but freedom of speech often suffers from public scrutiny. Both orally and in writing.